Fabrication and characterisation of microelectronic devices, circuits and systems III - Siek, Liter. (2008)
We present in this report the characterization of deep submicrometer (the device channel length ranges from 0.25um to 1.0um) lightly-doped drain (LDD) pMOSFETs operating in a Bi-MOS structure. The Bi-MOS structure is essentially a device operating with its sourcebody junction forward biased. Consequently, there is an additional current component, the lateral bipolar current, flwoing beneath the principle MOS current.